Katsuwonus pelamis Liver Powder Supplementation in Broilers: Small Intestinal and Skeletal Muscle Histology in Relation to Growth Performance - Rahmadian, D.; Shalihah, F.; Pasaribu, C. N. N.; Saragih, H. T. S. S. G. (Tropical Animal Science Journal, 2026)
Significant skipjack tuna (Katsuwonus pelamis) by-products are generated from Indonesia’s abundant marine resources, and utilizing nutrient-rich materials such as discarded liver for animal feed offers a sustainable alternative to environmentally harmful waste disposal. This study aimed to evaluate the effects of dietary supplementation with K. pelamis liver powder (KPP) on the histological structure of the small intestine and skeletal muscles, and growth performance in broilers. A total of 300 mixed-sex Cobb 500 day-old chicks were raised for 17 days and randomly assigned to four dietary treatments containing 0%, 1%, 3%, and 5% KPP. Growth performance was evaluated, and samples of the small intestine, skeletal muscles, and bone were collected on day 18 after an 8-hour fasting period and processed using standard histological procedures. Data were analyzed using one-way analysis of variance (ANOVA) followed by Duncan’s post hoc test. The results demonstrated that KPP supplementation enhanced multiple physiological variables in a concentration-dependent manner. Broilers receiving 3%–5% KPP showed significantly increased villus length, crypt depth, and goblet cell number and area across all small intestinal segments, along with higher skeletal muscle weight, fasciculus area, myofiber size, and myofiber number. Thoracic bone measurements were higher in KPP-fed groups. These improvements were accompanied by greater body weight gain and reduced feed conversion ratio (FCR), indicating enhanced growth performance, while hepatic histology showed no evidence of fatty liver. In conclusion, dietary inclusion of 3%–5% KPP supported broiler intestinal and skeletal muscle histology, improved growth performance, and promoted sustainable utilization of fishery by-products.